Chapter 1 Dimensions of European heritage and memory A framework introduction - Whitehead, Christopher (Taylor & Francis, 2019)
This book is a reflection on the politics of heritage in Europe at the present time, in a moment of pluralised conceptions of the political, social and demographic organisation proper to Europe. It is not a book that seeks to survey, define or characterise an enduring 'European heritage' as an entity, but rather to explore what heritage does - how it is understood, instrumentalised and what it enables - within what we will argue is a 'critical' moment for both identities and geopolitics in Europe.